NOVEL ROTOR POSITION EXTRACTION BASED ON ROTATING HIGH-FREQUENCY VOLTAGE INJECTION FOR PERMANENT MAGNET SYNCHRONOUS MACHINE DRIVES AT LOW OR ZERO SPEEDS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
A new procedure for rotor position extraction of salient-pole permanent magnet synchronous motors (PMSM) is presented in this paper. A carrier rotating signal is injected into the machine to measure its displacement using a high-frequency current. This method reduces computation time, simplifies the extraction model, and improves the displacement assessment error. This method is effective for surface mounted-permanent magnet synchronous motors (SPMSM) exhibiting small magnetic saliencies with sinusoidally distributed stator winding supplied by a space vector pulse wide modulation (SVPWM) voltage source inverter. The experimental results proved that the online phase shift compensation method could assess the rotor displacement, the speed, and the sensorless PMSM vector control operation with high accuracy. This method has shown its effectiveness for static and dynamic performance under various operating load conditions.
Keywords: Sensorless control; High frequency (HF) rotating carrier-signal injection; Surface-mounted permanent-magnet synchronous machines (SPMSM); Demodulation